Bioprosthetic tricuspid valve stenosis: a case series. Issue 3 (13th July 2019) - Hirata, Kazuhito; Tengan, Toshiho; Wake, Minoru; Takahashi, Takanori; Ishimine, Toru; Yasumoto, Hiroshi; Nakasu, Akio; Mototake, Hidemitsu
Abstract: Background: Bioprosthetic tricuspid valve stenosis is a late sequela of tricuspid valve replacement (TVR); however, detailed information regarding its clinical picture is lacking. Case summary: Thirty-one patients with bioprosthetic TVR (mean age: 60.5 ± 16.6 years, male/female: 11/20) were followed-up for 79.5 ± 49.1 months (14–188 months). Eleven patients developed bioprosthetic tricuspid valve stenosis (mean tricuspid gradient >5 mmHg) at a median interval of 96 months (interquartile range: 61–114 months). The mean tricuspid gradient at the time of tricuspid valve stenosis diagnosis was 10.9 ± 3.9 mmHg. Although the mid-term tricuspid valve stenosis-free survival was favourable (92.4% at 60 and 78.7% at 84 months), it had declined steeply to 31.5% by 120 months. Ten out of 11 tricuspid valve stenosis patients showed signs of right heart failure (RHF) as manifested by oedema and elevated jugular venous pressure, requiring moderate-to-high doses of diuretics. Diastolic rumble was audible in 10 patients. Five of the 11 tricuspid valve stenosis patients required redo TVR as a result of refractory RHF. Examination of the five excised bioprostheses showed pannus in four, fusion of the commissure in three, native valve attachment in two, and sclerosis in one. Detailed clinical pictures and pathology of the explanted valves in three cases that underwent surgery are presented in this case series. Discussion: Bioprosthetic tricuspid valve stenosis is not uncommon after 8 years. Tricuspid valve replacement performed at the second surgery was associated with a higher incidence of bioprosthetic tricuspid valve stenosis.